Innovative design and fabrication of generation IV nuclear fuel embedded with carbon nanotube. Issue 10 (July 2020) - Rao, P.T.; Prakash, Jyoti; Alexander, Rajath; Kaushal, Amit; Bahadur, Jitendra; Sen, Debasis; Dasgupta, Kinshuk
Abstract: The generation IV nuclear reactors Tri-structural isotropic (TRISO) fuel suffer failure due to internal pressure generation, corrosion by fission products and kernel migration under temperature gradient. An innovative fuel particle design was conceptualized and realized for the first time in literature by embedding multi-wall carbon nanotube (MWCNT) into porous buffer pyrolytic carbon layer (B.PyC) of TRISO particle to address above issues. MWCNT embedded in B.PyC was obtained by sequential coating using novel chemical vapor deposition reactor. Scanning electron microscopy shows ~15 μm uniformly dispersed MWCNT into B.PyC layer. Transmission electron microscopy and Raman Spectroscopy analysis of the deposited CNT revealed to be multi walled with good crystalline. Results of small angle scattering technique of the composite layer using X-ray and neutrons (SAXS/SANS) reveal better pore structure and could pave new vistas for TRISO fuel development. Intrinsic MWCNT features offer immense potential to mitigate various shortcoming of TRISO particle during actual Generation IV nuclear reactor operation.